PERAN CAREER PLATEAU DAN KEPUASAN KERJA DALAM MEMBENTUK TURNOVER INTENTION - Sijabat, Rauly (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2017)
High employee turnover rates are a classic problem that companies often encounter. The high turnover intensity can create instability and uncertainty about the condition of the workforce and the company itself. The results of previous research studies that have not been conclusive, led this study to examine the turnover intention with the career plateau approach and job satisfaction.Model and hypotheses were tested using primary data obtained through interviews using questionnaires on 100 respondents. The data obtained are then analyzed by using Structural Equation Modeling (SEM) analysis technique. The result of statistic test showed that career plateau proved to have a significant negative effect on job satisfaction, the career plateau proved to have a significant positive effect on turnover intention, and job satisfaction had a negative effect on turnover intention.